PERANCANGAN GAME EDUKASI DESCRIPTIVE TEXT BERBASIS MOBILE DI SMP MUHAMMADIYAH 1 GATAK - Ressa Melasovic; Siti Supeni; Yudhistiro Pandu Widoyoko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The objectives of this research are: 1) To determine the design of a mobile-based educational game for Descriptive text material at SMP Muhammadiyah 1 Gatak; 2) To determine the feasibility of the designed mobile-based educational game to be used as a learning medium in English language subjects for Descriptive text material at SMP Muhammadiyah 1 Gatak. This research was conducted at SMP Muhammadiyah 1 Gatak. This study uses the Research and Development method with the ADDIE development model. Data collection used observation, interviews, questionnaires, and documentation, and also employed the Blackbox Testing system and feasibility validation by experts, as well as student response results to provide feedback regarding the feasibility of the learning medium. Product feasibility validation was analyzed and converted using a Likert Scale to determine the percentage score for the feasibility of the